MOTIVASI EWOM PADA KONSUMEN KHALIFAH TOUR BANDUNG - Ghassani Salsabil Fasya Hikmat; Arianis Chan; Pratami Wulan Tresna (POLITEKNIK LP3I JAKARTA, 2024)
In the digital era, communication and information sharing have undergone a significant transformation. This has also impacted Word of Mouth (WOM), evolving from traditional methods to Electronic Word of Mouth (eWOM). Khalifah Tour, as an Umrah and Hajj travel company, utilizes the internet for promotion and encourages eWOM from its consumers. This study aims to identify the conditions and determine the most dominant motivations for consumers to send eWOM regarding Khalifah Tour. The research employs a descriptive quantitative method with 95 respondents from a population of 1695 individuals. Data were collected through questionnaires and analyzed using descriptive statistics and confirmatory factor analysis (CFA). The result of this research, Khalifah Tour consumers exhibit motivations for eWOM such as altruism and venting feelings. However, the most dominant motivation is self-enhancement. Khalifah Tour consumers demonstrate diverse motivations for engaging in eWOM, with self-enhancement being the most dominant, indicating a desire to portray their positive image to others. Key words: Electronic Word of Mouth, eWOM Motivation, Sending eWOM